2020
DOI: 10.1177/1941738120912846
|View full text |Cite
|
Sign up to set email alerts
|

One in 5 Athletes Sustain Reinjury Upon Return to High-Risk Sports After ACL Reconstruction: A Systematic Review in 1239 Athletes Younger Than 20 Years

Abstract: Context: Anterior cruciate ligament (ACL) reconstruction (ACLR) is frequently performed in patients younger than 20 years whose goal is to return to sport (RTS). Varying reinjury rates have been reported, and the factors responsible are unclear. Studies differ with regard to age, graft type, surgical techniques, postoperative rehabilitation, RTS guidelines, and methods used to determine ACL failures. Objective: To determine RTS rates; the effect of participation in high-risk sports, sex, and graft type on ACL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
67
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(71 citation statements)
references
References 111 publications
3
67
1
Order By: Relevance
“…Return to sport is of primary importance for a successful outcome following anterior cruciate ligament reconstruction (ACLR) [ 1 ]. However, athletes who do return to sport after ACLR are significantly more likely to sustain a second ACL injury compared to their previously uninjured counterparts [ 2 , 3 , 4 ], leading to inferior functional outcomes [ 5 ]. Hence, it is important to mitigate secondary injury risk through the identification and treatment of associated risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Return to sport is of primary importance for a successful outcome following anterior cruciate ligament reconstruction (ACLR) [ 1 ]. However, athletes who do return to sport after ACLR are significantly more likely to sustain a second ACL injury compared to their previously uninjured counterparts [ 2 , 3 , 4 ], leading to inferior functional outcomes [ 5 ]. Hence, it is important to mitigate secondary injury risk through the identification and treatment of associated risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Sports injuries around the knee, which are common in the paediatric age group, are treated surgically to prevent secondary injuries that may occur in the future. 5 It has been reported that 90% of the paediatric age group can return to sports with postoperative rehabilitation and in a shorter time than adults. 6 This is explained by the fact that the paediatric age group is less afraid of the risk of re-injury and has a better neuromuscular structure than adults.…”
Section: Introductionmentioning
confidence: 99%
“…Rupture is typically treated with surgical reconstruction to re-establish structural integrity of the knee joint, with the new ACL often crafted through harvesting of the patella, quadriceps, or semitendinosus/gracilis tendon. 7 Worldwide, the incidence of ACL reconstructive surgery is increasing, [8][9][10][11] with recent published evidence suggesting 20%-25% of patients will sustain a secondary injury, [12][13][14] and 36% develop knee joint osteoarthritis within 10 years following surgery. 15 Rupture and subsequent reconstructive surgery of the ACL is known to cause negative effects on the morphology and function of the quadriceps muscle group.…”
Section: Introductionmentioning
confidence: 99%